From the laboratory to the interstellar medium: a strategy to search for exotic molecules in space - Puzzarini, Cristina; Alessandrini, Silvia; Bizzocchi, Luca; Melosso, Mattia; Rivilla, Víctor M. (Frontiers in Astronomy and Space Sciences, 2023)
The chemistry of the interstellar medium occurs under extreme conditions and can lead to the formation of exotic molecules. These are species that on Earth are unstable and/or highly reactive. Their discovery in space is usually based on the astronomical observation of their rotational fingerprints, which requires an accurate laboratory investigation. This is based on a strategy that starts from the interplay of experiment and theory: state-of-the-art quantumchemical calculations are used to predict the relevant spectroscopic information required to guide the spectral recording, analysis and assignment. Rotational spectra measurements are then performed in the centimeter-/millimeter-/submillimeter-wave region, thereby exploiting efficient on-the-fly production protocols for exotic molecules. Subsequently, the spectral analysis leads to accurate spectroscopic parameters, which are then used for setting up accurate line catalogs for astronomical searches and detections. This review is based on the strategy developed and the results obtained at the ROT&Comp Lab of the University of Bologna.